Study Action Research: Literasi Akuntansi UMKM Berbasis ETAP dan Android Pada Era Covid-19 Normal Baru - Syahril Djaddang Djaddang; Sailendra S; M. Ardiansyah Syam; Susilawati Susilawati; Nunky P (Universitas Pancasila, 2021)
Abstract The purpose of implementing community service and research (action research) is to accelerate the process of developing an entrepreneurial culture; to increase the knowledge of MSMEs and Cooperatives in the digital world related to ETAP and Android-based accounting literacy through training, mentoring and research on MSME and cooperative actors in Bogor City. The Covid-19 pandemic and industrial disruption 4.0 have changed the socio-economic order; it also affects this type of industry. One of the challenges faced by MSMEs and Cooperatives today is the low accounting literacy and financial governance, coupled with the transformation of the socio-economic order from conventional to digital systems. One solution to increase the skill and knowledge of MSMEs and Cooperatives to the digital system related to accounting literacy and financial governance is through training, mentoring, and research. Pieces of training, mentoring, and research on MSMEs and Cooperative members are conducted by interacting directly through face-to-face and field observation. The implications of the results of this training, mentoring and study, recommend that the training and mentoring undertaken by academics in synergy with Cooperatives and MSMEs Government need to continue to be carried out on an ongoing basis. With continuous training and mentoring, literacy, and accounting skills based on SAK ETAP and financial governance based on Android, MSMEs can be improved to achieve the business's efficiency and performance. Especially in the era of the Covid-19 pandemic and the new normal, MSMEs are still available to exist and compete in the business competition.